Point of injury tourniquet application during Operation Protective Edge—What do we learn?. Issue 2 (August 2017) - Shlaifer, Amir; Yitzhak, Avraham; Baruch, Erez N.; Shina, Avi; Satanovsky, Alexandra; Shovali, Amiram; Almog, Ofer; Glassberg, Elon
Abstract : BACKGROUND: Hemorrhage is a leading cause of preventable death on the battlefield. Timely tourniquet application to massively bleeding extremity wounds is critical for casualty survival albeit with reported adverse effects to extremity integrity. The aim of this study was to describe the immediate- and short-term outcomes of point of injury (POI) tourniquet applications during "Operation Protective Edge" (OPE). METHODS: A case series study regarding tourniquet application at the POI during OPE was collected. The data gathered included reports by medical providers at the POI, aerial and land evacuation vehicles, and receiving hospitals. Variables collected included, the number of tourniquet applications, caregiver level, tourniquet type, limb characters, tourniquet effectiveness, in-hospital procedures, complications, and short-term limb outcome. RESULTS: During OPE, the Israeli Defense Forces Medical Corps treated 704 casualties. Of these, 90 casualties were treated with 119 tourniquets of which 79 survived. Penetrating trauma was the mechanism of injury in 97.8% (88 of 90) of the casualties. Injuries sustained from improvised explosive devices and shrapnel were related to the use of more than one tourniquet per casualty and per limb ( p = 0.034). The success rate of the first tourniquet was reported to be 70% (84 of 119), regardless of caregiver level ( p = 0.56), tourniquet type ( p = 0.16), or limb characters ( p = 0.48). Twenty-seven (25.7%) of 105 of the tourniquets were converted to direct pressure dressings enroute to receiving hospitals two of the conversions failed and thus a new tourniquet was applied. Fasciotomy was performed on eight casualties (a single limb in each). Vascular injury was presumed to be the indication for fasciotomy in three of these cases, in the other five limbs (6%, 5 of 85), no vascular involvement was discovered during surgery, and the fasciotomy is suspected as tourniquet related. 7%) 6 of 85) suffered from neurological sequela that could not be explained by their primary injury. Total complication rate was 11.7% (10 of 85) (one patient had both fasciotomy and neural complication without vascular injury). CONCLUSION: Tourniquet use on the battlefield is a simple method of eliminating preventable death, we believe that clinical practice guidelines should promote liberal use of tourniquets by trained combatants and medical personnel with abilities to convert to direct pressure hemorrhage control when possible since an unjustified tourniquet application risks low rates minor morbidity, whereas a justifiable tourniquet not applied may be lethal. LEVEL OF EVIDENCE: Epidemiologic study, level III; Therapeutic study, level IV.